The Effect Of Providing Preconception Nutrition Education Using The Think Pair Share (TPS) Model On Increasing Nutrition Knowledge And Attitudes Of The PPPM Baitul Makmur Surabaya Students - Susiawan, Kharisma Gita; Choirul Anna Nur Affifah (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Preconception nutrition education is an important initial step to improve knowledge and attitudes related to nutrition during the preconception period. This study aims to analyze the impact of counseling using the Think Pair Share (TPS) model and the lecture model with PowerPoint (PPT) on preconception nutrition for the students of PPPM Baitul Makmur Surabaya. The study adopted a quantitative research design with a quasi-experimental approach using a Pretest-Posttest Control Group Design, complemented by knowledge tests and attitude questionnaires. The study sample consisted of 40 participants, selected using Purposive Sampling, then divided into two groups, each consisting of 20 participants. The first group, the control group, received the lecture method with PowerPoint (PPT), while the second group, the experimental group, followed the Think Pair Share (TPS) method. Knowledge and attitude data from both groups were analyzed using the Paired Sample t-test and Independent Sample t-test. The results of the study show that both the PowerPoint (PPT) lecture method and the Think Pair Share (TPS) method are effective in improving preconception nutrition education outcomes. However, there were significant differences in the educational results achieved by the two methods, both in terms of knowledge (P=0.632) and attitude (P=0.733). This study measured the improvement in knowledge and attitudes related to preconception nutrition but did not address behavioral changes. Overall, the Think Pair Share (TPS) method was proven to be more efficient and effective in delivering preconception nutrition education, while the PowerPoint (PPT) lecture method is more suitable for application in a single meeting session due to the longer duration required.